The Urgency of Handling Bullying Toward Junior Hight Scholl Students - Danthy Meillya Sari; Frischa Meivilona Yendi (Universitas Negeri Padang, 2019)
Bullying is an action where someone or more are actioned/used to hit, pressure, and to make fall down of one’s mental. It is also to control other by violence. So, the victim of bullying can do nothing and recevie what ever done on him. Bullying is devided into three, physical, verbal or non physichal, and psychological bullying. Bullying can cause negatif impact on teeneger’s future life. The effect of bullying on psysic is physical healty like scare, bruise, headache, throatacha, cold, chest or even the death. Moreover, the long effect of that is the disturbance of physichological condition and bad social adaptation. Other, the fishting, long bad relationship, broken heart, feeling inconfidance on public and feeling of fear. It can be seen from the behavior presented like isolating them selves, less concentration, less succesfull, not socialization, scared, anger, calm, sensitive, isolated, rude feeling cool, incomfidance, worry and easy to get in sulted